Experimental Testing of PV Module Performance - Bošnjaković, Mladen; Stojkov, Marinko; Zlatunić, Boris (2021)
This study compares the manufacturer's technical data of several PV modules with real measured outdoor technical data. The irradiance effect on several PV modules is examined by the changing a tilt angle and comparing different meteorological situations of sky clearness (clouds) on the modules mounted outdoor and exposed to Sun. Also, the influence of temperature and dust on the performance of a PV panel is under research using measurement methods described in the paper. The measured current and voltage data at the clean surface of the PV module correspond to the declared data of the PV module manufacturer, and in the case of fouling of the module surface with dust, a power drop of 7.39% was measured.
Bibliografija
Summary.